Assessment of knowledge, attitude & practice of biomedical waste management among junior doctors during COVID-19 pandemic in a medical college & hospital of Eastern India - Hasina Banu; Swarnava Pramanick; Sinjita Dutta; Kumkum Bhattacharyya; Hirak Jyoti Raj (Al Ameen Journal of Medical Sciences)
Purpose: Bio-medical wastes (BMW) including COVID-19 wastes being important sources of transmission of infections and pollution need scientific handling and disposal. The study group intended to assess the knowledge, attitude and practice of junior doctors in this area. Methods: This descriptive, institution based, cross-sectional study was conducted for the period of three months; in a tertiary care hospital of eastern India using predesigned, pretested, semi-structured, two-part questionnaire. Knowledge assessment was done by ‘yes-no’ questionnaire. Assessment of attitude was accomplished by ‘five-point Likert’s scale’ and that of practice by answers like ‘never’, ‘sometimes’ and ‘always’ against preset questions. The data were analysed using Statistical Package for Social Sciences (SPSS) software. For all cases, p value < 0.05 was considered as statistically significant. Results: The majority of 128 participant junior doctors (45.3%) belonged to 26-30 years and nearly half were female. The study population comprised of 88 interns. Rest was post-graduate and post-doctoral trainees. Only 71(55.5%) participants had knowledge level above the mean poorest being in disposal of personal protective equipments. Favorable attitude was found among 73 (57.0%) only. The post graduate/doctoral residents maintained favorable attitude than interns. Adequate practices were found among 50% respondents. Residents observed more adequate practices (60.22%) than interns (31.25%). Only 37 (28.9%) junior doctors attended the training on waste management. Significant association was observed between the level of knowledge and the working category; with residents showing higher knowledge (χ2 =3.962, df=1, p=0.047). The attitude of residents were statistically better than interns (χ2=9.057, df=1, p=0.003). The residents and those who spent ≤ 08 hours in duty showed more compliant practices for BMW rules (χ2=14.626,df=2, p=0.001). Conclusion: Significant association between the level of knowledge and working category of the study population was noted in the study. Regular training and follow up is an absolute need for optimizing knowledge, attitude and practices.